(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Due to their capacity for localized medication administration and sustained release, bio adhesive systems are gaining more and more attention. As a result of the non-specific targeting, side effects are reduced. This review gives a general overview of the knowledge of bioadhesive drug delivery systems and the most current developments in their composition.